2011
DOI: 10.1039/c1lc00007a
|View full text |Cite
|
Sign up to set email alerts
|

Tracking and synchronization of the yeast cell cycle using dielectrophoretic opacity

Abstract: Cell cycle synchronization is an important tool for the study of the cell division stages and signalling. It provides homogeneous cell cultures that are of importance to develop and improve processes such as protein synthesis and drug screening. The main approach today is the use of metabolic agents that block the cell cycle at a particular phase and accumulate cells at this phase, disturbing the cell physiology. We provide here a non-invasive and label-free continuous cell sorting technique to analyze and syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
41
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 33 publications
2
41
0
Order By: Relevance
“…Both HDF and DLD are efficient, passive, and continuous techniques, but both require (i) highly complex features-130 branch channels for HDF [31], and complex and high-resolution arrays of posts with 13 different arrangements for DLD [29], and (ii) low flow rates-60 nL= min for Holm et al [30] and 2-3 L= min for Sugaya et al [31], consequently offering a low throughput that may be suitable for research applications but not for industrial-scale applications. Similarly, Valero et al performed shape-based sorting of yeast by balancing opposing DEP forces at multiple frequencies [32]. DEP requires the integration of active elements and a precise and reproducible control of the buffer conductivity between each experiment; both of these requirements complicate potential use beyond research applications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both HDF and DLD are efficient, passive, and continuous techniques, but both require (i) highly complex features-130 branch channels for HDF [31], and complex and high-resolution arrays of posts with 13 different arrangements for DLD [29], and (ii) low flow rates-60 nL= min for Holm et al [30] and 2-3 L= min for Sugaya et al [31], consequently offering a low throughput that may be suitable for research applications but not for industrial-scale applications. Similarly, Valero et al performed shape-based sorting of yeast by balancing opposing DEP forces at multiple frequencies [32]. DEP requires the integration of active elements and a precise and reproducible control of the buffer conductivity between each experiment; both of these requirements complicate potential use beyond research applications.…”
Section: Introductionmentioning
confidence: 99%
“…From these shape-based differences in focusing positions, we demonstrate passive and high-throughput separation using a particle's largest cross-sectional dimension as a distinguishing marker, independent of the smallest dimension of the particle. We apply this separation to the efficient and highthroughput sorting of budding yeast in view of cell-cycle synchronization (at rates of 60 L= min or 1500 cells=s compared to 100 cells=s in previous work [32]). The details of the particles and of the design of the devices and experimental methods appear in the Appendix.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies showed that the DEP characteristic of yeast cells varies widely, depending on the cell size, shape, and electric properties of cell contents and membrane. 18,31 In particular, the reported values of the crossover frequency where the value of Re(b) of the cell changes its sign (e.g., from negative to positive) have a range that spans one order of magnitude of the field frequency. This situation may be prominent for cultured yeast cells because of the budding process, which leads to a change in shape and size during growth.…”
Section: Resultsmentioning
confidence: 99%
“…17 A cell sorting technique using a combination of platinum electrodes with a photo-patterned insulator was proposed to analyze and synchronize yeast cell division. 18 Polymeric microfluidic device with integrated thick Carbon-Polydimethylsiloxane (C-PDMS) composite electrodes was proposed to carry out DEP trapping of low abundance biological cells. 19 In this study, by using C-PDMS electrodes as thick as a channel height, it was possible to extend the DEP force influence in the whole volume of the channel and maintaining high trapping efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…However, the throughput of ROT is limited, since it usually takes seconds to measure the rotation speed of a single cell. DEP, integrated within microfluidic systems, is more applicable to the manipulation and separation of single cells than their analysis [19,20]. In contrast, EIS enables the frequency-dependent multiparameter readout of cellular and even subcellular information in a high-throughput setting [21,22] or dynamically [23].…”
Section: Introductionmentioning
confidence: 99%